2019
DOI: 10.1038/s41598-019-53976-8
|View full text |Cite
|
Sign up to set email alerts
|

Lactation and menstruation shift the vaginal microbiota in captive rhesus monkeys to be more similar to the male urethral microbiota

Abstract: The vaginal microbiota of nonhuman primates differs substantially from humans in terms of Lactobacillus abundance, overall taxonomic diversity, and vaginal pH. Given these differences, it remains unclear in what way the nonhuman primate genital microbiota protects against pathogens, in particular sexually transmitted infections. Considering the effect that microbiota variations can have on disease acquisition and outcome, we examined endogenous and exogenous factors that influence the urogenital microbiota of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 37 publications
(77 reference statements)
0
14
0
Order By: Relevance
“…These changes are accompanied by changes in the microbiota, especially in the vagina and intestines ( Chen et al, 2017 ). A study of breastfeeding rhesus monkeys vaginal microbes during menstruation found that hormonal status affected the changes in microbiota ( Hallmaier-Wacker et al, 2019 ). It is generally believed that autoimmune diseases are the result of complex interactions between genetic and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes are accompanied by changes in the microbiota, especially in the vagina and intestines ( Chen et al, 2017 ). A study of breastfeeding rhesus monkeys vaginal microbes during menstruation found that hormonal status affected the changes in microbiota ( Hallmaier-Wacker et al, 2019 ). It is generally believed that autoimmune diseases are the result of complex interactions between genetic and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing the individual intestinal flora in mice showed that metabolic changes such as hyperglycemia, insulin resistance, and weight gain are related to changes in the composition of intestinal flora during pregnancy ( Curtis et al, 2012 ). Likewise, studies reported that the bacterial community of captive rhesus monkeys becomes more diversified with significantly different bacterial compositions during lactation and menstrual periods ( Hallmaier-Wacker et al, 2019 ). At present, there are rare reports about the changes in intestinal microbes during the menstrual cycle.…”
Section: Introductionmentioning
confidence: 99%
“…It remains unclear what biological factors contribute to Lactobacillus dominance and whether the cervicovaginal microbiome can be durably modulated by therapeutic intervention [ 85 ]. Hallmaier-Wacker et al found that menstruation is associated with a significant increase in alpha diversity and shift in beta-diversity among the rhesus vaginal microbiome [ 82 ]. Although vaginal community composition varies widely between individual macaques, Nugeyre et al identified taxa that cycled with progesterone levels within individual cynomolgus macaques and similarly, Rhoades et al observed that clinical markers of bacterial vaginosis differed significantly by menstrual status in rhesus macaques, as in women [ 80 •, 81 , 84 , 86 ].…”
Section: Sex and Age Mattermentioning
confidence: 99%
“…pallidum) and simian immunodeficiency virus (SIV) (Marra et al, 1992). In Chapter B3, our data show that endocrine-regulated processes (lactation/menstruation), cage-mate (sexual partners) relationships and group associations can significantly impact the urogenital microbiota (Hallmaier-Wacker et al, 2019a). Since these differences likely influence biomedical experiments, we urge for increased awareness of microbiota considerations of translational animal models.…”
Section: The Importance Of Baseline Data In Microbiome Analysismentioning
confidence: 89%
“…These findings have implications not only for disease ecology but also for the use of translational animal models (Kostic et al, 2013). In Chapter B3, we examined the genital microbiota of male and female rhesus monkeys (Hallmaier-Wacker et al, 2019a). Rhesus monkeys are commonly used translational animal models for infectious diseases, including sexually transmitted infections (Haus et al, 2014;Spear et al, 2010).…”
Section: The Importance Of Baseline Data In Microbiome Analysismentioning
confidence: 99%